Grammatical relations in Lohorung - Rai, Diwas (Journal of Nepalese Studies, 2025)
This study delves into the grammatical relations of Lohorung, a Tibeto-Burman language spoken in the Sangkhuwasabha district, Koshi Province. Lohorung exhibits an ergative-absolutive alignment with peripheral split-ergative patterns and follows a canonical SOV word order. Employing elicitation with native speakers and textual analysis, it examines subjects, objects, and peripheral arguments through verb agreement, case marking, and word order. Transitive verbs agree simultaneously with both subjects and objects, while intransitive verbs agree only with subjects, with many markers showing portmanteau forms. Singular, dual, and plural numbers are distinguished, and clusivity is overtly marked in first-person dual and plural forms. Equi-NP constructions are controlled by the matrix subject, reflexives are expressed with ‘self,’ zero anaphora follows preceding subjects, and causativization is marked morphologically with . The study also addresses nominal morphology, behavior-and-control properties, relativization, and co-reference in imperatives. These findings illustrate the systematic realization of grammatical relations in Lohorung, contributing to Tibeto-Burman typology and documentation of an endangered language.